Thermo-Mechanical Characterization of VGCF-Modified Adhesive for Bond between CFRP and Concrete Subjected to Combined Effect of Temperature and Humidity. Issue 12 (December 2014) - Al-Safy, R.A.; Al-Mahaidi, R.; Simon, G.P.; Habsuda, J.
Adhesives are employed in external strengthening of concrete structures by Carbon Fibre Reinforced Polymer (CFRP). Carbon-based composites are currently the most common type used to increase the strength of concrete members. The application of Carbon Fibre fabrics (CF fabric) to concrete members involves the use of a compatible bonding agent, and it is the modification of such bonding agents that is investigated in this paper. The investigation involves examining the effects of adding different concentrations of vapour-grown carbon nanofibres (VGCF) (0.5 wt%, 1 wt%, 1.5 wt% and 2 wt%) on the thermal and mechanical properties of the bonding agent. The effect of modification on the glass transition temperature and heat flow of the modified adhesive was explored using Differential Scanning Calorimetry (DSC) technique. It was found that Tg reduces slightly or remains the same with the addition of VGCF to Part A of the adhesive and the highest reduction in Tg was found when Part A was reinforced with 2 wt % VGCF. Agglomaration of the fibres was observed when VGCF was introduced into MBrace® Saturant epoxy adhesive using the speed mixer and a random orientation for the fibres was noted within the epoxy matrix. Peeling-off of CF fabric was the common failure mode as the loaded CFRP/concrete system was subjected to the combined effect of temperature and humidity after short periods of exposure to such severe conditions.